Cultural Immersion: Developing a Community of Practice of Teachers and Aboriginal Community Members - Burgess, Cathie; Cavanagh, Paddy (Pat) (The Australian Journal of Indigenous Education, 2015)
A lack of teacher awareness of the cultural and historical background of Aboriginal students has long been recognised as a major causative factor in the failure of Australian schools to fully engage Aboriginal students and deliver equitable educational outcomes for them. Using Wenger's communities of practice framework, this paper analyses the effectiveness of the Connecting to Country (CTC) program in addressing this issue in New South Wales (NSW) schools whereby Aboriginal community members design and deliver professional learning for teachers. Qualitative and quantitative data from 14 case studies suggest that the CTC program has had a dramatic impact on the attitudes of teachers to Aboriginal students, on their ability to establish relationships with the local Aboriginal community and on their willingness to adapt curriculum and pedagogy to better meet the needs of their students. As Aboriginal community members and teachers developed communities of practice, new approaches to Aboriginal student pedagogies were imagined through a sense of joint enterprise, mutuality and shared repertoire, empowering all participants in the CTC journey. Implications from this research highlight the importance of teacher professional learning delivered by Aboriginal people, Aboriginal community engagement in local schools and addressing deficit discourses about Aboriginal students and their families.